4(x-8)+x=26

Simple and best practice solution for 4(x-8)+x=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-8)+x=26 equation:


Simplifying
4(x + -8) + x = 26

Reorder the terms:
4(-8 + x) + x = 26
(-8 * 4 + x * 4) + x = 26
(-32 + 4x) + x = 26

Combine like terms: 4x + x = 5x
-32 + 5x = 26

Solving
-32 + 5x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + 5x = 26 + 32

Combine like terms: -32 + 32 = 0
0 + 5x = 26 + 32
5x = 26 + 32

Combine like terms: 26 + 32 = 58
5x = 58

Divide each side by '5'.
x = 11.6

Simplifying
x = 11.6

See similar equations:

| 4(1+w)=3(4+w) | | -4+5+6v=1+5v+3 | | 3(c+4)=5+2c | | (4x-1)+(2x+1)=8x-4 | | 3i^2+15/6-3i | | 7(x-1)=6x | | x^2+15/6-x | | 3z+3-z=10+z-5 | | 36=2(3.14)r | | 3x-13=2x | | 7g+1-5g=-8 | | -X^2-12X-20=0 | | 73.14/23 | | x/3+12/1=-x/3 | | -[5z-(15z+6)]=6+(9z+0) | | (-11-16)+5= | | 5x/7+12/7=-13/7 | | -4(y+2)=-3y-1 | | 1-6x-13= | | -4(x-6)=-4x+24 | | ln(3x+6)=3 | | 41.5/5 | | 5x+2=8x-4x | | 3y+7x=13 | | 5x+4+4x=31 | | 10.98/3.4 | | x+x+1=x+2+24 | | y=x^2+8x-11 | | 35/8x12/15 | | -1.2r=6.0 | | x^2+8x-11=y | | 4=2y+105 |

Equations solver categories